THE THE EFFECT OF BTD, ROA, LEVERAGE, COMPANY SIZE AND DEFERRED TAXES ON TAX AVOIDANCE IN THE FINANCIAL SECTOR - Yusriva, Salma; Paramitalaksmi, Ratri (Global Financial Accounting Journal, 2024)
This study aims to determine the Influence of BTD, ROA, Leverage, Company Size and Deferred Tax on Tax Avoidance in the Financial Sector. The method applied is multiple linear regression with data from annual financial statements. The sample was taken from companies in the financial sector on the IDX for the 2020-2023 period which was selected by the purposive sampling method. The results of the study stated that the variables BTD, ROA, Company Size and Deferred Tax did not affect tax avoidance, but Leverage had a significant effect. This research is expected to provide insight for investors, regulators, and corporations in understanding the factors that affect tax avoiudance, as well as its implications for tax policy in Indonesia.